AB0090 INHERITED DEFICIT OF PROTEOGLYCAN MIMICKING SEPTIC ARTHRITIS. (June 2019) - Florio, Angelo; Papa, Riccardo; Caorsi, Roberta; Consolaro, Alessandro; Gastaldi, Roberto; Ravelli, Angelo; Gattorno, Marco; Picco, Paolo; Rinne, Tuula
Abstract : Background: Aggrecanopathies (AP) are a heterogeneous group of skeletal disorders caused by ACAN gene mutations leading to dysfunction of a proteoglycan called aggrecan that plays a pivotal role in the organization of the extracellular matrix of the growth-plate cartilage. Clinically, patients with AP display bone dysplasias ranging from severe spondyloepimetaphyseal dysplasia to familial cases of osteochondritis dissecans (OCD) associated with short stature and typical facial dysmorphisms 1 . Objectives: Herein we report a patient with AP referred to our Institute for an inflammatory articular involvement mimicking a septic arthritis. Methods: Molecular analysis of the ACAN gene was performed using Sanger sequencing method. Results: A 14-year-old boy displayed pain and swelling at the right elbow. Echo-scan revealed an effusion in both coronoid and olecranon recess. Acute phase reactants were negative. A month later, since non-steroidal anti-inflammatory drugs were administered without benefit, the patient was admitted in our Institute. On physical examination, acute arthritis at the right elbow was noted: it appeared painful, warm, and not erythematous. Laboratory test showed slight elevation of acute phase reactant (C reactive protein 1.7 mg/dl, normal value <0.5). Arthrocentesis was performed and sterile synovial fluid was found. Magnetic resonance images displayed a bone fragment detachment from the humeral condyle of the right elbow with synovium thickening and persistent effusion: the diagnosis of OCD was pointed out. The patient showed minor dysmorphisms (i.e. dolicocephaly, hypotelorism, arched palate and brachydactyly of the IV finger of both hands) and parents reported a previous episode of OCD when he was 12: at that time, symptoms resolved with non-weightbearing and non-steroidal anti-inflammatory therapy after few days. Furthermore, the patient went under regular endocrinologist follow-up for short stature since he was 8. At the age of 10, his height was 123 cm, SDS 2.4, and growth hormone (GH) stimulation tests showed partial response to insulin tolerance test (GH peak 6.27 ng/mL). Bone age at the X-Ray of right hand and wrist was delayed of 12 months. Human recombinant GH replacement therapy was administered without significant growth-velocity improvement. Although the patient came to observation because of suspected elbow septic arthritis, we re-considered the diagnosis: namely, i. recurrent episodes of OCD; ii. short stature that was poorly responsive to the human recombinant GH treatment, iii. mild skeletal and facial dysmorphisms, led us to hypothesize a form of aggrecanopathy. Molecular analysis of the ACAN gene revealed the novel missense variant c.6970T>C, p.Trp2324Arg in the G3 domain of the protein. Notably, another mutation of the G3 domain (c.7249G>A) has been previously related to aggrecanopathy2. Intra-familial molecular analysis allowed us to detect the same gene variant in other three subjects (the mother and 2 siblings) affected only by brachydactily and short stature. Conclusion: A patient carrying a novel mutation of the ACAN gene presented an atypical form of aggrecanopathy mimicking inflammatory and/or septic arthritis associated with slight short stature and bone dysmorphisms. Further studies are needed to investigate a possible role of this novel ACAN gene variant in the inflammatory articular involvement. References: [1] [Gibson BG, Briggs MD.The aggrecanopathies; an evolving phenotypic spectrum of human genetic skeletal diseases Orphanet J Rare Dis. 2016; 11: 86.] [2] [E.L. Stattin, F. Wiklund, K. Lindblom, et al.A missense mutation in the aggrecan C-type lectin domain disrupts extracellular matrix interactions and causes dominant familial osteochondritis dissecans. Am. J. Hum. Genet., 86 (2010), pp.126-137] Disclosure of Interests: Angelo Florio: None declared, Riccardo Papa: None declared, Roberta Caorsi: None declared, Alessandro Consolaro Grant/research support from: AbbVie, Pfizer, Roberto Gastaldi : None declared, Angelo Ravelli Grant/research support from: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Consultant for: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Speakers bureau: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Marco Gattorno Grant/research support from: MG has received unrestricted grants from Sobi and Novartis, Paolo Picco: None declared, Tuula Rinne: None declared